2014
DOI: 10.1115/1.4027829
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Development of Secondary Features in a Richtmyer–Meshkov Instability Driven Flow

Abstract: Richtmyer–Meshkov instability (RMI) has long been the subject of interest for analytical, numerical, and experimental studies. In comparing results of experiment with numerics, it is important to understand the limitations of experimental techniques inherent in the chosen method(s) of data acquisition. We discuss results of an experiment where a laminar, gravity-driven column of heavy gas is injected into surrounding light gas and accelerated by a planar shock. A popular and well-studied method of flow visuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Downstream, a spike of dense material ejected from the cylinder moves with a high subsonic velocity (∼ 0.3M in terms of the local Mach number [29]). Vortex structures at the end of the spike have been observed in experiment ("lion's tail" [29]), however, the adjacent wakelike structure best visible in the centerline plane of Fig. 5 could not be visualized because there was no fluorescent tracer to track it.…”
Section: Resultsmentioning
confidence: 99%
“…Downstream, a spike of dense material ejected from the cylinder moves with a high subsonic velocity (∼ 0.3M in terms of the local Mach number [29]). Vortex structures at the end of the spike have been observed in experiment ("lion's tail" [29]), however, the adjacent wakelike structure best visible in the centerline plane of Fig. 5 could not be visualized because there was no fluorescent tracer to track it.…”
Section: Resultsmentioning
confidence: 99%
“…The Richtmyer-Meshkov instability has been investigated in numerical and experimental studies. Bernard et al [25] experimentally investigated the primary features of flow developing after a shock acceleration and found that a well-studied method of flow visualization did not produce a flow pattern that matched the numerical model. Liu & Lu [26] investigated the flow instability of viscoelastic annular liquid jets in a radial electric field and found that the jets with reasonable parameters had greater instability.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used in several studies of shock wave interactions with a multiphase or heavy gas column [6,7]. The shock tube itself can operate in a horizontal position or can be inclined to any angle θ, up to 45…”
Section: Experimental Arrangement and Diagnosticsmentioning
confidence: 99%
“…The Atwood number is A = (ρ 2 − ρ 1 )/(ρ 2 + ρ 1 ), where ρ 2 and ρ 1 are the densities of the heavy and light gas, respectively. For SF 6 and air, A = 0.67.…”
Section: Experimental Arrangement and Diagnosticsmentioning
confidence: 99%